'Secondary foreign policy' through the prism of cross-border governance in the US–Canada Pacific Northwest border region. Issue 3 (27th May 2017) - Dupeyron, Bruno
ABSTRACT: This paper seeks to revisit the notion of 'secondary foreign policy' through the analysis of cross-border governance in the US–Canada Pacific Northwest border region. Although pro-open border organizations in this borderland support secondary foreign policy principles, they collectively need to adjust them, due to the increasing border securitization on the Canada–US border. In other words, the militarization of the border should not affect mutually beneficial cross-border interactions and relations. Using Neil Fligstein and Doug McAdam's 'field theory', this paper analyses how the field of cross-border governance in the Pacific Northwest tends to evolve in a new geopolitical context after 9/11, in which free trade and cross-border flows are subjected to growing 'primary foreign policy' security imperatives. The specific focus on two cross-border organizations reveals how primary and secondary foreign policy actors seek to work on joint cross-border projects, in spite of contrasting interests and steady blind spots.